1997
DOI: 10.1002/j.2161-007x.1997.tb00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Humor Appreciation and Counselor Self‐Perceptions

Abstract: This study examined the relationship between humor appreciation and self‐perceptions of high school guidance counselors. Results indicated that humor appreciation was unrelated to self‐perceived counselor effectiveness, and that male and female counselors enjoyed similar types of humor. Counselors described their humor preferences as being extroverted, realistic, intelligent, and enjoying lighthearted and offbeat humor. Finally, counselors with more education perceived themselves as having less of a sense of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…One of the main advantages of using humor in counseling is that it allows the counselor to convey a sense of genuineness and empathy to the client. One of the main disadvantages of using humor in counseling inappropriately is that its use might inadvertently allow clients to avoid areas of conflict or may restrict their expression of emotion (Kush, 1997). Therefore, humor in the therapeutic process can have both desired and undesired consequences, and this seems to depend a great deal on how humor is introduced by the counselor and how it is used in counseling.…”
Section: Humor and Counselingmentioning
confidence: 99%
“…One of the main advantages of using humor in counseling is that it allows the counselor to convey a sense of genuineness and empathy to the client. One of the main disadvantages of using humor in counseling inappropriately is that its use might inadvertently allow clients to avoid areas of conflict or may restrict their expression of emotion (Kush, 1997). Therefore, humor in the therapeutic process can have both desired and undesired consequences, and this seems to depend a great deal on how humor is introduced by the counselor and how it is used in counseling.…”
Section: Humor and Counselingmentioning
confidence: 99%
“…They also point out that poor timing in the use of humour and insensitivity to the immediate context can make the counsellor appear incompetent and insensitive. In an interesting aside, Kush ( 1997), reporting on the results of a study on humour appreciation and counsellor self-perceptions, found that counsellors perceive that their sense of humour diminishes as their levels of education increase. Kush warns that if counsellors, especially in the high-school setting, perceive themselves as becoming less humorous, so may the students.…”
Section: Humour and Comfortmentioning
confidence: 99%